Comparison of the Performance of Iranian Azeri-Speaking Children Based on Iran and Reference Bayley III Norms - Hasani Khiabani, Nahideh; Barzegar, Mohammad; Raeisi, Sina; Jalalin Chaleshtori , Marzieh; Heidarabady, Seifollah; Bahari Gharehgoz, Ali (Iranian Journal of Child Neurology, 2022)
Abstract Objectives The aim of this study was comparing of performance of Iranian children on the Bayley Scales of Infant and Toddler Development- third edition with the standardized norms of Iran and United State. Materials & Methods A total of 248 Iranian children at the ages of 1-42 months were participated in this study. The Bayley Scales of Infant and Toddler Development- third edition was administered to evaluate the cognitive, language and motor development of these children. Results The scaled scores of the study group were higher based on the reference norms in receptive communication, fine motor, and gross motor subtests. The scaled scores were variable in expressive communication and cognitive subtests. The differences were significant for receptive communication and fine motor subtests (P<0.05). Using the reference norms instead of Iran norms resulted in under-referral regarding receptive communication and fine motor subtests. More children scored below 1 and 2 SD using Iran norms in comparison to those reported for using the reference norms. Conclusion Iran norms differ significantly from the reference norms over two subscales. It is recommended to use population-specific norms to identify children with developmental delay and early intervention